2016
DOI: 10.1111/exd.13110
|View full text |Cite
|
Sign up to set email alerts
|

Does Schwann cell dedifferentiation originate dermal neurofibromas?

Abstract: H Y P O T H E S I S L E T T E R3. Although loss of Nf1 is required for neurofibroma development, it is not sufficient and tumor microenvironment plays a key role in this process. Poorly regulated wound healing has been described in NF1 haploinsufficient tissues, S8 again highlighting a possible relationship between wounding and tumor initiation. | HYPOTHESISIn the skin, terminal SCs ensheathe peripheral nerve endings. S9These SCs are able to dedifferentiate into a progenitor-like state in response to trauma or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In support of this hypothesis, another human study by Iribar et al found Schwann cell precursor marker CDH19 and Schwann cell dedifferentiation marker Sox2 were significantly upregulated in neurofibromas from diagnostic patients. They posited that the dedifferentiation of Schwann cells played a role in human dermal neurofibroma development, while dedifferentiated Schwann cells were suggested to form hSKPs [ 60 ]. Taken as a whole, further work is needed in order to illuminate clear understanding of hSKPs biological safety, although most studies concluded hSKPs as “a safe grafting source.”…”
Section: Therapeutic Potential Of Hskpsmentioning
confidence: 99%
“…In support of this hypothesis, another human study by Iribar et al found Schwann cell precursor marker CDH19 and Schwann cell dedifferentiation marker Sox2 were significantly upregulated in neurofibromas from diagnostic patients. They posited that the dedifferentiation of Schwann cells played a role in human dermal neurofibroma development, while dedifferentiated Schwann cells were suggested to form hSKPs [ 60 ]. Taken as a whole, further work is needed in order to illuminate clear understanding of hSKPs biological safety, although most studies concluded hSKPs as “a safe grafting source.”…”
Section: Therapeutic Potential Of Hskpsmentioning
confidence: 99%
“…More research should be made on investigating the costimulatory molecule expression, the immunophenotype in inflammatory environment, and the immunosuppressive features both in vitro and in vivo . In addition, it is now believed that stem cells with neurogenic capacities ascribed to dedifferentiated Schwann cells presenting in spheroid culture [40, 50, 51], although it is still unclear whether the diversity will affect the biotechnological applications of hSKPs or not. In the current study, we are limited in our experimental ability to address these issues on tSKPs.…”
Section: Discussionmentioning
confidence: 99%
“…Schwann cells are associated with aspects of cutaneous homeostasis and are known to play a role in multiple diseases (see Table for details). We now have significant experimental evidence that activated SCs contribute to wound healing, [ ] neurofibromatosis, [ ] leprosy [ ] and melanoma growth and invasion. [ ] Taken together with the known functions of SCs, these studies have highlighted a previous unappreciated role of SCs in cutaneous biology and pathology.…”
Section: Role Of Scs In Human Skin Physiology and Clinical Dermatologymentioning
confidence: 99%